KUALITAS LAYANAN, NILAI PELANGGAN, DAN PROMOSI TERHADAP KEPUASAN PELANGGAN KERETA API DALAM MENGGUNAKAN ACCESS BY KAI - Muhammad Sani Arsyadi; Rauly Sijabat; Rita Meiriyanti (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
The case study from this study found findings that showed that the Access by KAI application in October 2024 received a rating of 2.5/5.0, this value is the lowest rating of other train ticket booking applications such as Traveloka and tiket.com which received a rating of 4.8/5.0 on the play store application store, therefore the researcher wants to know "how customer satisfaction is using the Access by KAI application". The researcher wants to conduct research on this problem, by developing an empirical method to explain the variables that affect customer satisfaction by using data obtained from the play store app store and distributing questionnaires to the general public randomly. The test was carried out using the Statistical Product and Service Solutions (SPSS) approach. The test results found that the quality of service was proven to be significant and positive to customer satisfaction, customer assessments were not proven to have a significant effect and negative on customer satisfaction, promotions were not proven to be significant and negative to customer satisfaction.